Prevalence of Dental Caries among Primary School Children of Kathmandu District- A Pilot Study - Khanal, Sunita; Bhattarai, Rosina; Rao, G Nagaraja; Shrestha, Sujita (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Worldwide, 60 to 90% of school children have experienced dental caries with higher prevalence in Asian and Latin American countries and poor dental and oral health and untreated oral disease can have a significant impact on quality of life according to WHO report. The objectives of the study were to assess the prevalence of dental caries both in deciduous and permanent teeth and to compare total decayed, filled teeth surfaces among primary school children of Kathmandu from both government and private schools and to find the percentage of first permanent molars affected with dental caries. Materials & Methods: A cross sectional study was conducted among two Government and two Private Primary School Children in Kathmandu district. Total sample were 468 children. Required permission were obtained from concerned authorities. WHO accepted indices for assessing caries designed by Henry T Klein, Carrole E Palmer and Knutson J.W was used. SPSS 20 version software was used for data analysis. Results: Among 468 primary school children examined, 224 were from Government and 244 were from Private school. The prevalence of dental caries was 62 % and more deciduous teeth were decayed. The decayed, filled teeth surfaces in Private and Government school was statistically significant (p=0.000) but gender wise prevalence was statistically insignificant (p=0.303). Among 1st Permanent Molars teeth examined 85% were decayed. Conclusion: This pilot study shows prevalence of dental caries more in deciduous teeth. Among the permanent teeth affected, first permanent molars are in high number.